Visual performance and patient-reported outcomes of an EDF intraocular lens compared with a monofocal intraocular lens: randomized trial - Stefan Palkovits; Manuel Ruiss; Caroline Pilwachs; Johannes Zeilinger; Stefan Georgiev; Oliver Findl (Journal of Cataract & Refractive Surgery, 2026)
Purpose: To evaluate clinical performance and visual outcomes of the Acunex Vario AN6V in comparison with the monofocal version, the Acunex AN6. Setting: Department of Ophthalmology, Hanusch Hospital, Vienna, Austria. Design: Prospective, randomized, monocenter trial. Methods: Patients undergoing bilateral cataract surgery were randomized to receive extended depth of field (EDF) intraocular lens (IOL), the Acunex Vario AN6V (EDF group) or the monofocal IOL Acunex AN6 (monofocal group). Primary outcome was spectacle independence 6 months postoperatively. Furthermore, uncorrected and corrected distance, intermediate and near visual acuity, stereo vision, defocus curves, and rate of photopic phenomena were assessed. Results: 50 patients were included in the study, of whom 42 completed the 2 months and 35 the 6-month visit. 2 months after the procedure, a significantly higher proportion of patients in the EDF were spectacle-free during near tasks than in the monofocal group (37.5% vs 5.3%). Uncorrected and corrected distance intermediate (UIVA and DCIVA) as well as near (UNVA and DCNVA) visual acuities were significantly better in the EDF group (UIVA: 0.09 ± 0.12 vs 0.16 ± 0.07; P = .035; DCIVA: 0.12 ± 0.10 vs 0.16 ± 0.08; P = .03; UIVA: 0.24 ± 0.12 vs 0.37 ± 0.11; P = .001; DCNVA: 0.24 ± 0.12 vs 0.37 ± 0.11; P = .001) Furthermore, the EDF group had a larger range of defocus. Stereo vision and the occurrence of photopic phenomena were comparable between both groups. Conclusions: In comparison with the monofocal version, the EDF IOL AN6V demonstrated greater spectacle independence and significant enhancement in both intermediate and near visual acuities. Notably, the incidence, severity, and degree of perceived dysphotopsia were similar in both groups.